2018
DOI: 10.1523/eneuro.0132-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Cycle Stages Modulate Alzheimer-Related Cognitive and Brain Network Alterations in Female Mice

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 93 publications
2
23
0
Order By: Relevance
“…Although female rodents do not undergo menopause, they do experience a period of altered estrous cycling (Guimarães et al, 2015) followed by persistently low estrogen levels at old ages (Felicio et al, 1984), similar to peri-and post-menopause in women. Findings from these models are in agreement with two possibilities in humans: (1) reduced estrogen exposure in adult females exacerbates disease progression, as in J20 mice (Box 1) (Broestl et al, 2018); and/or (2) the organizational effects of sex hormones during neurodevelopment have lasting effects that increase susceptibility to neurodegenerative disease later in life, as in 3xTgAD mice (Box 1) (Carroll et al, 2010). For more information, we direct the reader to a review summarizing findings from LOAD animal models consistent and inconsistent with the sex differences observed in humans (Fisher et al, 2018).…”
Section: Findings From Animal Modelssupporting
confidence: 78%
“…Although female rodents do not undergo menopause, they do experience a period of altered estrous cycling (Guimarães et al, 2015) followed by persistently low estrogen levels at old ages (Felicio et al, 1984), similar to peri-and post-menopause in women. Findings from these models are in agreement with two possibilities in humans: (1) reduced estrogen exposure in adult females exacerbates disease progression, as in J20 mice (Box 1) (Broestl et al, 2018); and/or (2) the organizational effects of sex hormones during neurodevelopment have lasting effects that increase susceptibility to neurodegenerative disease later in life, as in 3xTgAD mice (Box 1) (Carroll et al, 2010). For more information, we direct the reader to a review summarizing findings from LOAD animal models consistent and inconsistent with the sex differences observed in humans (Fisher et al, 2018).…”
Section: Findings From Animal Modelssupporting
confidence: 78%
“…This phenotypic difference between male and female 5xFAD mice is also consistent with the higher incidence of AD in female compared to male human subjects. Interestingly, TLQP-21 is also known to be involved in the regulation of the reproductive cycle in female rodents [18,21], and Broestl and colleagues have observed that female hAPP mice in estrogendominant cycle stages have worsened AD-related network dysfunction and cognitive impairments, while in contrast, those in progesterone-dominant stages and after gonadectomy have attenuated AD-related deficits [104]. Failure to detect equivalent effects of TLQP-21 treatment in male and female 5xFAD could also reflect sex-related differences in microglial function, which could be associated with transcriptional and translational differences between male and female microglia, including in C3aR1 expression levels which are higher in males [105,106].…”
Section: Discussionmentioning
confidence: 99%
“…Several possible explanations may account for the combined effects of sex and APOE [27][28][29][30]. A potential mechanism could be that oestradiol promotes synaptic sprouting in response to injury through an APOE-dependent mechanism [27].…”
Section: Discussionmentioning
confidence: 99%
“…A potential mechanism could be that oestradiol promotes synaptic sprouting in response to injury through an APOE-dependent mechanism [27]. Additionally, oestrogen might promote neural function under normal conditions, but exacerbate dysfunction when network activity is disrupted [28].…”
Section: Discussionmentioning
confidence: 99%